Synthesis And Anticancer Screening Of Novel Spiro[Chroman-2,4′- Piperidin]-4-One Derivatives With Apoptosis-Inducing Activity - Shaimaa A. Abdelatef, Mohammed T. El-Saadi, Noha H. Amin, Ahmed H. Abdelazeem & , Khaled R.A. Abdellatif & (Journal of Applied Pharmaceutical Science, 2018)
A novel series of spiro[chroman-2,4′-piperidin]-4-one derivatives was synthesized and evaluated as cytotoxic agents against three human cancer cell lines; MCF-7 (human breast carcinoma), A2780 (human ovarian cancer) and HT-29 (human colorectal adenocarcinoma) using MTT assay. Compound 16 with a sulfonyl spacer exhibited the most potent activity with IC50 values between 0.31 and 5.62 μM. However, the trimethoxyphenyl derivative 15 was the least potent with IC50 values between 18.77 and 47.05 μM. The most active compound 16 was selected for further mechanistic studies, which revealed that it induced more than three folds early apoptosis in MCF-7 cells treated for 24 h. Addi-tionally, it increased MCF-7 cells in the sub-G1 and G2-M cell cycle phases, following the same treatment duration. Together, these compounds could be promising cytotoxic candidates, thus further structural optimization, in vitro and in vivo studies are recommended to be developed into potential cytotoxic agents.
Keywords: Spiro[chroman-2,4′-piperidin]-4-one, cytotoxic, MTT,apoptosis, cell cycle analysis.